OPTIMALISASI LAHAN PEKARANGAN UNTUK PERTANIAN DI DESA JADA BAHRIN, KECAMATAN MERAWANG KABUPATEN BANGKA PROVINSI KEPULAUAN BANGKA BELITUNG - Gigih Ibnu Prayoga (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2016)
Food sovereignty is an effort to fulfill food needs in a self-sufficient manner. Fulfilling food needs starting from the household level is considered capable of improving national food security. Land utilization up to the yard level is needed in order to achieve food sovereignty in an area. Thematic Community Service Program (KKN) was conducted in Jada Bahrin village as an effort to help achieve food sovereignty in the village. The expected output targets are: 1. Encouraging the optimization of the use of yard land for agricultural cultivation; 2. Facilitating the transfer of technology of food crop and horticultural cultivation systems and integrated pest control from the university level to the community; 3. Development of community independence, especially farmer groups in farming activities; 4. Improving the knowledge and skills of farmers in the utilization of yard land. The main activities carried out to achieve these output targets are: 1. Training on hydroponic cultivation system; 2. Training on making compost based on household waste; 3. Application of integrated pest control technology; 4. Training on making food products made from local plants; 5. Implementation of Village Farmer Consultation Activities. The results obtained during the Thematic KKN are: 1. Utilization of hydroponic systems in the village hall and residents' yards; 2. Utilization of household waste as compost raw material. 3. Pest control using papaya leaves; 4. Making dodol made from kemilik as a typical food of Jada Bahrin village; 5. Implementation of farmer meetings in 3 villages, namely Jada Bahrin, Balunijuk, and Kimak villages. In addition, it is expected that program sustainability will be achieved such as The utilization of Jada Bahrin Village's agricultural location as an example village for the application of simple hydroponic technology, and the establishment of a farmer clinic that can help farmers overcome pests and plant diseases.